The DASH diet - beneficial impacts on cardiovascular system and even more - Maj, Dominik; Wieteska, Małgorzata; Gorecka, Adrianna; Gorajek, Anna; Wacławska, Monika (Journal of Education, Health and Sport, 2022)
Introduction and objective: Hypertension is the main preventable risk factor for both cardiovascular disease and premature death globally. Estimates suggest that almost one in three adults suffered from hypertension in 2010. This clinical entity can lead to different severe complications such as heart failure or stroke. Data shows that blood pressure(BP) reduction below currently recommended leads to a significant decrease of the risk of cardiovascular disease. The aim of the study is to review recent knowledge and beneficial impacts of Dietary Approaches to Stop Hypertension(DASH) diet, which is considered to decrease blood pressure. The information used in the presented analysis was obtained by searching academic research databases: Google Scholar and PubMed. An abbreviated description of the state of knowledge: The DASH diet is one of well known dietary patterns. It is rich in fruits, whole grain and low-fat diary products. Basing on the data, it can significantly decrease BP, what leads to a reduction of cardiovascular disease risk. Furthermore, high adherence to the DASH diet is associated with a lower risk of mortality from all cancer types and lower risk of colon cancer development, as well as with a lower risk of type 2 diabetes development. Summary: The DASH diet is a commonly prescribed dietary pattern, which is known of its effectiveness in BP reduction. Additional research confirms its several different health benefits including decrease of the cardiovascular risk. Finally, the research give the recommendation, that the DASH diet should be pursued to increase the antihypertensive drug treatment effectiveness, but also to delay hypertension onset.